Eco-innovation and Performance: The Role of Relational Capability - Magdalena PICHLAK (Communications of International Proceedings, 2021)
The primary purpose of the paper is to analyze the impact of relational capabilities on efficient eco-innovation activities conducted by Polish companies. Environmental innovations are described two-dimensionally, considering the level of novelty of technological eco-innovations generated by companies (i.e., radical and incremental). Similarly, the two-dimensional conceptualization of relational capabilities covers the external and internal relational capabilities. The conducted research was carried out among the 54 most innovative Polish companies that develop novel eco-innovative technological solutions. The hierarchical regression analysis shows that collaboration with customers, suppliers, competitors, universities, research institutes, and agencies is critical for developing radical eco-innovation. Simultaneously, efficient internal communication, sharing of knowledge and experience between organizational members, and collaborative learning of employees working together are enough to create incremental eco-innovation successfully.
Keywords: Eco-Innovation; Relational Capability; Performance; Moderation Model.